Ionic conductivity of biopolymer electrolytes based on seaweed kappa-carrageenan / S. Rudhziah ...[et al.]. - S., Rudhziah; N.A.C., Apandi; R.H.Y., Subban; N. S., Mohamed (2018)
Seaweed kappa-carrageenan was used as host polymer to prepare biopolymer electrolyte films. Solid biopolymer electrolytes based on seaweed kappa-carrageenan were prepared by incorporation of ammonium nitrate in various weight percentage. The films were examined using Fourier transform infrared spectroscopy and electrochemical impedance spectroscopy. The results of Fourier transform infrared spectroscopy proved the occurrence of complexation between the biopolymer and the salt. The ionic conductivity of the electrolyte increased with increase salt concentration. The maximum ionc conductivity value of 1.41 × 10-4 S cm-1 was achieved for the film containing 50 wt % ammonium nitrate. The temperature-conductivity plot of the polymer electrolytes was found to obey Arrhenius equation.